2012
DOI: 10.1007/s00396-012-2642-x
|View full text |Cite
|
Sign up to set email alerts
|

Semi-batch control over functional group distributions in thermoresponsive microgels

Abstract: Thermosensitive poly(N-isopropylacrylamide-comethacrylic acid) (poly(NIPAM-co-MAA)) microgels were prepared via semi-batch free radical copolymerization in which the functional monomer (methacrylic acid) was continuously fed into the reaction vessel at various speeds. Microgels with the same bulk MAA contents (and thus the same overall compositions) but different radial functional group distributions were produced, with batch copolymerizations resulting in core-localized functional groups, fastfeed semi-batch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 53 publications
(56 reference statements)
3
25
0
1
Order By: Relevance
“…Other core shell structures can be obtained by controlling the monomer feed. 27 This was, for example, shown by Hoare and coworkers. This group prepared different thermosensitive poly(N-isopropylacrylamide-co-methacrylic acid) (poly(NIPAM-co-MAA)) microgels using a semibatch free radical copolymerization.…”
Section: Microgels With Other Polymer Coresmentioning
confidence: 68%
See 1 more Smart Citation
“…Other core shell structures can be obtained by controlling the monomer feed. 27 This was, for example, shown by Hoare and coworkers. This group prepared different thermosensitive poly(N-isopropylacrylamide-co-methacrylic acid) (poly(NIPAM-co-MAA)) microgels using a semibatch free radical copolymerization.…”
Section: Microgels With Other Polymer Coresmentioning
confidence: 68%
“…Other core shell structures can be obtained by controlling the monomer feed . This was, for example, shown by Hoare and coworkers.…”
Section: Purely Polymer Based Core–shell Microgelsmentioning
confidence: 91%
“…Also, Hirotsu et al observed that an increase in the ionic strength resulted in an increase in the VPTT for PNIPAM microgels copolymerized with sodium acrylate. On the other hand, Chang et al observed a decrease in VPTT at higher salt concentrations. However, the nature of the system should be taken into account, since in that case the thermosensitivity was induced by PNIPAM and the thermal behavior was not affected by the increase in the p K a .…”
Section: Resultsmentioning
confidence: 92%
“…These results suggest that there is another opposite effect hindering the protonation of amine groups: further protonation enhanced the polymer charge density, resulting in a larger electrostatic repulsive force. This could be attributed to the polyelectrolyte effect . In the presence of adjacent ionized functional groups, the ionization of amine groups at higher degrees of ionization was inhibited due to the polyelectrolyte effect.…”
Section: Resultsmentioning
confidence: 99%
“…The prepolymerization temperature greatly influenced the polymerization reaction rate constant and half-life of the initiator [20][21], which would greatly influence the distribution of the chain segment of the copolymer and the resulting properties of the copolymer foam [22]. The distribution of the chain segment and the conversion ratio of the monomer were also greatly influenced by feeding method of the monomer, which would reduce the implosion possibility of bulk polymerization [23][24][25][26]. Different feeding methods were employed to adjust the conversion ratio of the monomer and further adjust the composition of the copolymer in this study.…”
Section: Introductionmentioning
confidence: 99%